2004
DOI: 10.1093/humupd/dmh035
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone replacement therapy: current trends and future directions

Abstract: Male hypogonadism is characterized by abnormally low serum testosterone levels associated with typical symptoms, including mood disturbance, sexual dysfunction, decreased muscle mass and strength, and decreased bone mineral density. By restoring serum testosterone levels to the normal range using testosterone replacement therapy, many of these symptoms can be relieved. For many years, injectable testosterone esters or surgically implanted testosterone pellets have been the preferred treatment for male hypogona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 67 publications
2
139
0
2
Order By: Relevance
“…This has also been confirmed in other studies establishing symptom-specific thresholds of androgen levels [1,2,[25][26][27]. It, therefore, comes as no surprise that there is a significant variation among clinics and European countries in their application of threshold values of testosterone signifying hypogonadism which range from 7.5 to 12.0 nmol L -1 [28]. Almost certainly a factor in this observation is that physicians in different countries will have different concepts of what constitute the core symptoms of hypogonadism.…”
Section: Thresholds and Dose-response Relationships Of Androgen Effectssupporting
confidence: 72%
“…This has also been confirmed in other studies establishing symptom-specific thresholds of androgen levels [1,2,[25][26][27]. It, therefore, comes as no surprise that there is a significant variation among clinics and European countries in their application of threshold values of testosterone signifying hypogonadism which range from 7.5 to 12.0 nmol L -1 [28]. Almost certainly a factor in this observation is that physicians in different countries will have different concepts of what constitute the core symptoms of hypogonadism.…”
Section: Thresholds and Dose-response Relationships Of Androgen Effectssupporting
confidence: 72%
“…In this study, we have only used biochemical parameters in defining hypogonadism. The levels of 10 nmol/l for total testosterone and 10 IU/l for LH are generally accepted as useful markers of hypogonadism in younger males (22). A shortcoming in current study is the change in the methods for testosterone and LH measurements.…”
Section: Discussionmentioning
confidence: 94%
“…Review studies have suggested that the most frequently observed health benefits of TRT include improvements in sexual function, mood and quality of life, muscle strength, and cognitive function; and increased bone mineral density (Nieschlag et al 2004;Bassil et al 2009;Fernández-Balsells et al 2010). These studies have, however, also indicated that TRT may increase the risk of prostate and breast cancers, liver toxicity and tumors, testicular atrophy, infertility, gynecomastia, erythrocytosis, and skin diseases; may worsen benign prostatic hypertrophy; and could exacerbate sleep apnea.…”
Section: Effects Of Testosteronementioning
confidence: 99%